2005
DOI: 10.1210/jc.2004-1627
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Noncontrast Computed Tomography Attenuation Value (Hounsfield Units) to Differentiate Adrenal Adenomas/Hyperplasias from Nonadenomas: Cleveland Clinic Experience

Abstract: Radiological characterization of an adrenal tumor as adenoma may decrease the need for follow-up imaging studies, biopsies, and unnecessary adrenalectomies. We retrospectively reviewed 299 adrenalectomies in 290 patients at Cleveland Clinic Foundation over a recent 5-yr period to assess the value of noncontrast Hounsfield units (HU) in characterizing whether an adrenal mass is adenoma or nonadenoma. The mean (+/- SD) HU value for the adrenocortical adenoma/hyperplasia group was 16.2 +/- 13.6 and significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
153
2
14

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(178 citation statements)
references
References 67 publications
8
153
2
14
Order By: Relevance
“…To test the effectiveness of the different proposed cortisol cut-off after the 1-mg DST by using Bayesan analysis we had to define a priori the probability of autonomous cortisol secretion based on observed alterations in the tests used to assess the function of the HPA axis. We acknowledge that such a definition is arbitrary, but the presence of at least two alterations of the HPA axis has been widely used in previous work (14,22,23,24). Our data confirm that only a cut-point at 138 nmol/l achieves an incremental diagnostic effectiveness to detect functional adrenal autonomy.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…To test the effectiveness of the different proposed cortisol cut-off after the 1-mg DST by using Bayesan analysis we had to define a priori the probability of autonomous cortisol secretion based on observed alterations in the tests used to assess the function of the HPA axis. We acknowledge that such a definition is arbitrary, but the presence of at least two alterations of the HPA axis has been widely used in previous work (14,22,23,24). Our data confirm that only a cut-point at 138 nmol/l achieves an incremental diagnostic effectiveness to detect functional adrenal autonomy.…”
Section: Discussionsupporting
confidence: 61%
“…an adrenal mass detected serendipitously by an imaging work-up performed for the evaluation of unrelated diseases in patients without clear signs or symptoms suggestive of adrenal disease), exclusion criteria a priori were severe or paroxysmal arterial hypertension, hypokalemia (<3.5 mEq/L), clinical signs of hypercortisolism or hyperandrogenism, and patients with previous or current history of malignancies known to metastasize commonly in the adrenal glands (4,12). When not histologically proven, the diagnosis of cortical adenoma rested on the following computed tomography (CT) criteria: size less than 6.0 cm, regular shape with well-defined margins, homogenous and hypodense content (13,14). The diagnosis of adenoma was confirmed by a repeat CT scan after 6 months showing no significant increase in mass size, or change in mass density, in any patient (4,12).…”
Section: Subjectsmentioning
confidence: 99%
“…A number of studies have shown that the unenhanced CT attenuation value is the most reliable tool in the differentiation of benign and malignant lesions (7,16). Adrenocortical adenomas are usually rich in lipids and show low attenuation values, whereas high-density masses are suspected for malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Her urinary metanephrines were repeatedly negative on two collections (0.86 µg/mg creatinine and 0.8 µg/mg creatinine; normal value: < 1.0 µg/mg creatinine). However, computerized tomography of the abdomen showed a rightsided adrenal mass; non-contrast images revealed a density of 36 Hounsfield units, findings that are highly suggestive for a pheochromocytoma (11). Moreover, this mass was also positive on MIBG scintigraphy.…”
Section: Sequence Analysismentioning
confidence: 93%